Homeland Security: Roles and Missions for United States Northern Command - Knight, William (Library of Congress. Congressional Research Service., 2008)
This report outlines the organizational structure of United States Northern Command (NORTHCOM), explains how NORTHCOM contributes to homeland security through the interagency process, and summarizes NORTHCOM's international relationships with Canada and Mexico. Some issues for Congress involving NORTHCOM include Department of Defense (DOD) reorganization and the Unified Command Plan, improving interagency relationships, NORTHCOM's increased reliance on reserve component service members, the ongoing Cheyenne Mountain Operations Center realignment, and the allocation of resources necessary for NORTHCOM to successfully plan for and execute its assigned missions.